(untitled) (Journal of Dhaka Medical College, 2018)
Context: Osteoarthritis is primarily a disease of cartilage as it is characterized by the degradation of hyaline cartilage in the joints. It is believed to be a dynamic disease that reflects the balance between destruction and repair. Clinically, there is pain, swelling of joints and limitation of motion. Pathological disease is characterized by focal erosive lesions, cartilage destruction, subchondral sclerosis, cyst formation and large osteophyte at the margin of the joints. The objectives of management of osteoarthritis (OA) of the knee are to relieve pain, maintain or improve mobility, and minimize disability. Treatment options include non -pharmacologic intervention, drug therapy, and surgery. Different modalities of physical therapy have been shown to help improve clinical symptoms and function of knee OA with fewer adverse effects. Transcutaneous electrical nerve stimulation (TENS) is among these non invasive therapies which have been used to treat a variety of painful acute and chronic conditions including osteoarthritis. Material and Methods: This randomized clinical trial was conducted on 60 (sixty) patients attending in Physical Medicine and Rehabilitation department of Dhaka Medical College Hospital, who were suffering from knee osteoarthritis. The patients were randomly divided into two groups, Group-A and Group-B. The patients were evaluated clinically and data was collected from both groups in a pre designed data collection sheet for visual analogue scale (VAS) on Pain, 50 feet walking time in seconds and tenderness index in every two weeks interval from the first visit for up to 6 weeks. All the data were analyzed by SPSS version 16.1. Result : The present study showed pain, tenderness and walking time were significantly improved in Group A who were treated with TENS, NSAID & ADL instructions than in Group B who were treated with NSAID & ADL instructions after 6 weeks( P<0.05). Conclusion: The results of this study suggest that application of TENS along with NSAIDs and ADL instructions is more effective in reduction of pain and improving functional performances in patients with knee osteoarthritis than the drug only treatment. J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 62-67